Automatic Light Design Using Light Sensors - Samsu Tuwongkesong; Edwin Timothy Werdhinata Waleleng; Muhammad Rivai Sugiarto (Publikasi Indonesia, 2025)
People prefer to do things outside the home, such as taking care of themselves, outdoor activities until late at night, and generally unkempt house conditions, greatly increasing the likelihood of community crimes that include outdoor activities such as light maintenance, outdoor activities until late at night, and generally unkempt house conditions, greatly increasing the likelihood of criminal acts. Automatic technology is the solution to this problem, a type of household equipment that can be cleaned and maintained automatically. A descriptive approach is used, where researchers use reliable and systematic data to describe a phenomenon. for the use of Arduino Uno software that can provide instructions to turn on and detect lights. As an automatic indicator, the light sensor connected to the relay is very sensitive to the light resistance measured by the light sensor. The bulb will turn off automatically if the light sensor detects a number of more than 200 at the beginning of the day. Automatic lights can be operated via a Light Dependent Resistor (LDR) sensor so that the lights automatically turn on based on the resistance value measured by the sensor and timer. This is one way to develop a system in the event of a system disruption or seasonal rain. The timer can remember to adjust and set the lights as needed.